Serum Reproductive hormone levels in male symptomatic HIV/AIDS patients on Antiretroviral therapy negative to Malaria parasite in Nnewi, Anambra State, Nigeria - Ezeugwunne, Priscilla Ifeoma; Ogbodo, Chukwuemeka Emmanuel; Analike, Adamma Rosemary; Obi-Ezeani, Nwando Chikaodili; Onuora, Joy Ifeoma; Oguaka, Nwabunwanne Victor; Amah, Kalu Ubou; Ugwu, Chukwuemeka Michael; Onyenekwe, Chinedum Charles; Ahaneku, Eberendu Joseph (Asian Journal of Medical Sciences, 2019)
Background: AIDS is an endemic disease that causes death among young adults worldwide especially in Nigeria. Aims and Objectives: This study investigated the serum reproductive hormone levels in symptomatic HIV/AIDS male subjects on ART who are negative to malaria parasite in Nnewi, Anambra State, Nigeria. Materials and Methods: A total of 274 adult male participants aged between 18 and 60 years were randomly recruited, and grouped into: symptomatic HIV (stage 11) infected male participants on ART (A: n=69), Symptomatic HIV subjects not on ART (B: n= 69), Asymptomatic HIV positive subjects (C: n= 68) and HIV seronegative subjects (D: n= 68). Serum was used to assay for PSA, LH, FSH, Estrogen, Testosterone, Progesterone and Prolactin levels. Analysis of variance and student t-test were used for data analyses. Results: The serum levels of PSA, FSH, Estrogen, Testosterone, Progesterone and Prolactin were significantly different amongst the groups at p<0.05 respectively. There were significantly higher levels of PSA, Estrogen, Progesterone but lower levels of Testosterone and Prolactin in subjects on ART compared with control at p<0.05 respectively. There were significantly higher levels of PSA, FSH, Estrogen,Progesterone but lower levels of Testosterone in subjects not on ART compared with control at p<0.05 respectively. Conclusion: The reduction on serum levels of Testosterone and higher levels in FSH, PSA, Estrogen, and Progesterone may reveal presence of hypogonadism, primary testicular failure, prostate abnormalities such as cancer and hyperprogesteronaemia, in symptomatic HIV positives.